Extranuclear SUMOylation in Neurons. Issue 4 (April 2018) - Henley, Jeremy M.; Carmichael, Ruth E.; Wilkinson, Kevin A.
Abstract : Post-translational modification of substrate proteins by SUMO conjugation regulates a diverse array of cellular processes. While predominantly a nuclear protein modification, there is a growing appreciation that SUMOylation of proteins outside the nucleus plays direct roles in controlling synaptic transmission, neuronal excitability, and adaptive responses to cell stress. Furthermore, alterations in protein SUMOylation are observed in a wide range of neurological and neurodegenerative diseases, and several extranuclear disease-associated proteins have been shown to be directly SUMOylated. Here, focusing mainly on SUMOylation of synaptic and mitochondrial proteins, we outline recent developments and discoveries, and present our opinion as to the most exciting avenues for future research to define how SUMOylation of extranuclear proteins regulates neuronal and synaptic function. Highlights: SUMOylation and deSUMOylation of proteins outside the nucleus play key roles in neuronal function and viability. SUMOylation acts as a molecular switch to alter inter- and/or intramolecular interactions of substrate proteins to change their localisation, stability, and/or activity. Multiple pre- and postsynaptic, as well as mitochondrial and mitochondria-associated, proteins have been identified as SUMO substrates. SUMOylation and deSUMOylation of target proteins is stringently regulated in response to synaptic activity and cell stress. Dysregulation of SUMOylation of extranuclear proteins is strongly implicated in neurological and neurodegenerative diseases.